2015
DOI: 10.1085/jgp.201411288
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the late component of the cardiac L-type Ca2+ current to suppress early afterdepolarizations

Abstract: Decreasing the amplitude of the late component of the cardiac L-type Ca2+ channel current suppresses early afterdepolarizations, thereby decreasing the risk of arrhythmias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
93
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(96 citation statements)
references
References 44 publications
(72 reference statements)
3
93
0
Order By: Relevance
“…In addition, EADs are promoted by spontaneous Ca 2+ release from the SR that triggers the inward Na + /Ca 2+ -exchange current (Choi et al, 2002). Consistent with these mechanisms, in mammalian ventricular myocytes, EADs can be abolished by reducing the size of the window I CaL (Madhvani et al, 2015) or by blocking the SR Ca 2+ release with ryanodine (Volders et al, 1997). Interestingly, in crucian carp ventricular myocytes, cold acclimation (+4°C) reduces the size of the maximum window I CaL from ca.…”
Section: Avoidance Of Cardiac Arrhythmiamentioning
confidence: 79%
“…In addition, EADs are promoted by spontaneous Ca 2+ release from the SR that triggers the inward Na + /Ca 2+ -exchange current (Choi et al, 2002). Consistent with these mechanisms, in mammalian ventricular myocytes, EADs can be abolished by reducing the size of the window I CaL (Madhvani et al, 2015) or by blocking the SR Ca 2+ release with ryanodine (Volders et al, 1997). Interestingly, in crucian carp ventricular myocytes, cold acclimation (+4°C) reduces the size of the maximum window I CaL from ca.…”
Section: Avoidance Of Cardiac Arrhythmiamentioning
confidence: 79%
“…Activated CaMKII phosphorylates cardiac Na and Ca channels enhancing the highly arrhythmogenic late Na (I Na-L ) [14] and the late L-type Ca (I Ca-L ) [15] currents. Isolated myocytes and dynamic-clamp experiments have shown that an isolated increase of either of these two late inward currents promotes cellular early and delayed afterdepolarizations (EADs and DADs respectively) causing rapid triggered activity [16,17]. Indeed inhibition of the I Na-L with the highly potent (IC 50 =0.143 μM) and selective inhibitor GS-967 [18] suppresses EADs in isolated atrial myocytes [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…L-type calcium channels are modulated by both voltageand calcium-dependent inactivation gating mechanisms. 1 Although the mechanism by which intravenous calcium appeared to suppress EADs in this case is unclear, calcium could lead to a slightly higher plateau of the AP, leaving only a prolonged APD but attenuating EADs. Intravenous calcium might also attenuate EADs by increased calciumdependent inactivation of the late component of L-type calcium channels.…”
Section: Response To Ecg Challengementioning
confidence: 76%
“…The late component of the L-type Ca 2+ current may be especially relevant to EADs. 1 EADs are oscillations of the cell membrane and require inward calcium and outward potassium currents to be properly matched in amplitude and timing. L-type calcium channels are a promising therapeutic target to normalize AP duration (APD) and suppress EADs.…”
Section: Response To Ecg Challengementioning
confidence: 99%
See 1 more Smart Citation